Pengenalan dan Pemberian Makanan Tambahan Puding Kelor Sebagai Upaya Pencegahan Stunting - Lilik Sofiatus Solikhah; Friesta Sarani; Hikma Tullah; Imelda Andryani; Irfa Arfiani; Jurana Jurana; Kamila KH Djiha; Sri Ramadhani; Ummu Rizkiyanti; Yuni Karmila (Universitas Pahlawan Tuanku Tambusai, 2023)
One of the nutritional problems that is still quite high in Indonesia is stunting. Stunting is a growth and development disorder in children caused by chronic malnutrition and recurrent infections, characterized by height for age (TB/U) or body length for age (PB/U) less than -2 SD. The prevalence of stunting under five in Kalora Village, Kinovaro District, Sigi Regency has increased by 9% from 2020-2021. The purpose of this activity is to help integrate the implementation of interventions to reduce stunting in Kinovaro District, especially Kalora Village, by carrying out nutritional interventions in the form of demonstrating the making of Moringa pudding to Posyandu cadres, introducing and providing additional food for Moringa pudding accompanied by providing information related to the benefits of consuming Moringa to toddlers, school-age children, teenagers or WUS, and pregnant women. The demonstration activity went smoothly and the provision of Moringa pudding was well received.